Determinants of Employee Retention Intention in Nepalese Commercial Banks - Pokharel, Santosh (DEPAN, 2024)
The research was carried with the purpose of detecting elements of staff retention intention and its impact on commercial banks of Nepal. The research was based on perception 190 employees consisting both assistant and officer level of Everest bank limited and Nepal Bangladesh bank (NABIL Bank) limited. Close ended questionnaire was employed to collect the Data. Analysis has been done using mix of data analysis tools that encompasses descriptive, correlation, regression, independent sample t-test and One-Way ANOVA. Based on the analysis, the study has drawn some facts having managerial implications in the field of human resource management. It can be claimed that retention is a complex phenomenon that requires strategic orientation. Although challenges are persistent in relation to management of all factors but management of compensation, career opportunities, organization prestige, supervisor support and work life balance are most considerable from the perspective of banks and employees.